One health ethics - Capps, Benjamin ca. 20./21. Jh. (Bioethics, 2022)
One health has brought to the fore connections—between human culture and nature—that underlie healthy (and unhealthy) ecological niches. Like other emerging environmental concepts—eco-health, one medicine and planetary health—one health merges scientific evidence with reasons for sustaining a healthy environment. This narrative is not new, but the importance of a cogent way of thinking about nature in ways that allow us to ameliorate harms brought about by human activities has become a theme of the Anthropocene. Many societies face seemingly insurmountable crises, brought about by a collective failure to foster ethical forms of environmental health. The following essay is an egalitarian reimagining of one health ethics. Undertaking this task is of considerable philosophical importance, because solving the problem of denotation—asking what is one health?—could change our rational view of nature for the betterment of humankind and our Earthly companions.